1998
DOI: 10.1111/j.1751-1097.1998.tb09460.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Tetra (m-hydroxyphenyl)chlorin in Human Plasma and Individualized Light Dosimetry in Photodynamic Therapy

Abstract: The pharmacokinetics of the photosensitizer 5,10,15,20-tetra(m-hydroxyphenyl)chlorin (mTHPC) was investigated in the plasma of 20 patients by absorption and fluorescence spectroscopy. The temporal behavior was characterized by a rapid decrease in concentration during the first minutes after intravenous injection of 0.15 mg/kg mTHPC. A minimum concentration in the plasma was reached after about 45 min. The drug concentration then increased again, attaining a maximum after about 10 h, after which it decreased ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 27 publications
(22 reference statements)
1
28
1
Order By: Relevance
“…This shows that the clearance of m-THPC is faster than that of Photofrin. Similar pharmacokinetic analyses in humans have determined half-lives as 452 h for Photofrin (Brown et al, 1992) and 30 h for m-THPC (Glanzmann et al, 1998).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This shows that the clearance of m-THPC is faster than that of Photofrin. Similar pharmacokinetic analyses in humans have determined half-lives as 452 h for Photofrin (Brown et al, 1992) and 30 h for m-THPC (Glanzmann et al, 1998).…”
Section: Discussionmentioning
confidence: 78%
“…Preclinical results indicate that the efficacy of m-THPC is related to both the drug dose and the interval between administration and illumination (Ris et al, 1993a, b). However, the efficacy is also complicated by many in vivo interactions, such as aggregation and protein binding (Glanzmann et al, 1998;Hopkinson et al, 1999). This study aims to correlate m-THPC pharmacokinetics with PDT efficacy and the mechanism of PDT damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial rapid drug clearance phase, which is seen in rodents, does not occur in humans. Pharmacokinetic profiles for Foscan demonstrate an unusual delayed plasma peak at about 10 h after bolus injection, with subsequent elimination half-lives in the range of 30 -60 h (Braichotte et al, 1995;Glanzmann et al, 1998). The plasma drug concentrations therefore remain at levels of at least 500 ng ml À1 for up to 96 h after a standard dose of 0.15 mg kg À1 Foscan.…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy with meta(tetrahydroxyphenyl)chlorin (mTHPC) has been shown in clinical trials to be a safe and effective treatment of early malignancy in the upper aerodigestive tract, the bronchi and the oesophagus (Grosjean et al, 1996b;Savary et al, 1997). Numerous studies have shown that mTHPC, like other anti-cancer drugs (McLoed and We, 1995), has high inter-patient variability for accumulation of the drug in normal or malignant tissues Glanzmann et al, 1998). This variability is probably a major factor in the large range of tissue responses to PDT in different patients who have undergone treatment under identical conditions (e.g., drug dose, light dose, light dose rate, time delay after drug administration).…”
mentioning
confidence: 99%